Levels of PCDDs and PCDFs in two kinds of fast foods in Korea - Kim, Y; Yang, SH; Lee, SY; Kim, M (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
We initiated an attempt to gather preliminary Korean fast food data on the concentrations, whole weight and international toxic equivalent (TEQ), in two kinds of fast foods, hamburger and fried chicken. The levels of polychlorinated dibenzo-p-dioxins/polychlorinated dibenzofurans (PCDDs/PCDFs) in hamburgers are detected to be lower than in fried chickens. Total TEQ level of PCDDs in fried chicken is 47.45 times higher than in hamburger. In case of PCDFs, it is 48.61 times. Even though these are compared to the only one brand and three samples each, we think that these high levels of PCDDs/PCDFs in fried chicken are very important data because of the potentially increasing daily intake. If we continue to survey for PCDDs/PCDFs in fast foods more even, especially fried chicken, these data will be useful to calculate the estimated daily intake of TEQ levels of PCDDs/PCDFs in Korea. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: DIBENZOFURAN LEVELS; UNITED-STATES; VIETNAM; DIOXINS; GERMANY; SOUTH